High serum levels of fatty acid-binding protein 7 in diabetic rats with experimental sepsis - Emerson R Martins; Thais M de Lima; Hermes V Barbeiro; Marcel C César Machado; Fabiano Pinheiro da Silva (SAGE Publishing, 2018)
Sepsis is a disease that affects a wide variety of individuals, including the young, the elderly, and those admitted to the hospital with diverse acute or chronic conditions. Because sepsis is such a heterogeneous disease, some researchers believe that personalized medicine may represent a promising means of improving the prognosis for certain patients. Of those who develop sepsis, diabetic patients remain a significant proportion, because diabetes is a metabolic disorder that is associated with disturbances in the immune system, which facilitates bacterial infections. Fatty acid-binding proteins (FABPs) are a family of transport proteins with an important role in metabolism; therefore, we decided to measure their levels in diabetic rats, as part of a search for a novel biomarker of sepsis. Diabetes was experimentally induced in male Wistar rats, some of which then underwent cecal ligation and puncture, and the levels of FABP4 and FABP7 were measured in their serum and key tissues. Serum FABP7 levels in diabetic septic rats were significantly higher than those in non-diabetic septic rats. Consequently, we propose that FABP7 should be further investigated as a potential biomarker of sepsis in diabetic patients.